2002
DOI: 10.1667/0033-7587(2002)157[0032:eoxrib]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of X-Ray-Induced Breaks in DNA Bound to Molecules Containing Platinum: A Possible Application to Hadrontherapy

Abstract: ВВЕДЕНИЕКлючевым моментом для повышения тера-певтической ýффективности лучевой терапии является контрастность, которая заключается в максимизации дозы ионизирующего излучения, подведенной к опухоли и минимизации дозы об-лучения, полученной здоровыми тканями и орга-нами. Широко используемые современные мето-ды лучевой терапии основаны на геометрическом нацеливании излучения на опухоль. Такое наце-ливание реализуется за счет коллимации и фо-УДК 616-006.6:615.849:001.89 DOI 10.20538/1682616-006.6:615.849:001.89 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 17 publications
0
37
0
Order By: Relevance
“…Subsequent work explored analogous cleavage reactions for DNA in solution [61] and showed that, as with the dry film studies, platinated DNA was cleaved approximately twice as much as unplatinated DNA. However, the effect of DMSO as a solution radical scavenger and studies of variable wavelength excitation led researchers to conclude that hydroxyl radical formation is the major cleavage mechanism.…”
Section: Nucleic Acid Cleavagementioning
confidence: 91%
“…Subsequent work explored analogous cleavage reactions for DNA in solution [61] and showed that, as with the dry film studies, platinated DNA was cleaved approximately twice as much as unplatinated DNA. However, the effect of DMSO as a solution radical scavenger and studies of variable wavelength excitation led researchers to conclude that hydroxyl radical formation is the major cleavage mechanism.…”
Section: Nucleic Acid Cleavagementioning
confidence: 91%
“…[2][3][4] In addition, NPs composed of high-Z elements such as noble metals or lanthanides amplify the effect of radiation treatment. 5 This phenomenon, which was first evidenced for platinum complexes combined with highenergy photons 6,7 and fast ions, 8 was later demonstrated for gold NPs (AuNPs) 9 and platinum NPs (PtNPs) 10 in combination with photons or fast ions. Subsequent simulation studies have led to first insights into this amplification effect.…”
Section: Introductionmentioning
confidence: 94%
“…For detailed analysis of x-ray absorption by heavy atoms, absorption of a mono-energetic photon should be examined using a tunable energy source such as synchrotron facilities. Use of a mono-energetic microbeam in radiobiology is already in progress elsewhere [18].…”
Section: Resultsmentioning
confidence: 99%